An Overview of Molecular Mechanism of Nephrotic Syndrome - Juliana Reis Machado; Laura Penna Rocha; Precil Diego Miranda de Menezes Neves; Eliângela de Castro Cobô; Marcos Vinícius Silva; Lúcio Roberto Castellano; Rosana Rosa Miranda Corrêa; Marlene Antônia Reis (International Journal of Nephrology)
Podocytopathies (minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS)) together with membranous nephropathy are the main causes of nephrotic syndrome. Some changes on the expression of nephrin, podocin, TGF-β, and slit diaphragm components as well as transcription factors and transmembrane proteins have been demonstrated in podocytopathies. Considering the pathogenesis of proteinuria, some elucidations have been directed towards the involvement of epithelial-mesenchymal transition. Moreover, the usefulness of some markers such as TGF-β1, nephrin, synaptopodin, dystroglycans, and malondialdehyde have been determined in the differentiation between MCD and FSGS. Experimental models and human samples indicated an essential role of autoantibodies in membranous glomerulonephritis, kidney damage, and proteinuria events. Megalin and phospholipase-A2-receptor have been described as antigens responsible for the formation of the subepithelial immune complexes and renal disease occurrence. In addition, the complement system seems to play a key role in basal membrane damage and in the development of proteinuria in membranous nephropathy. This paper focuses on the common molecular changes involved in the development of nephrotic proteinuria.